2012
DOI: 10.1080/02786826.2012.685113
|View full text |Cite
|
Sign up to set email alerts
|

First Surface Measurement of Cloud Condensation Nuclei over Kanpur, IGP: Role of Long Range Transport

Abstract: INTRODUCTIONThe concentration of cloud condensation nuclei (CCN) can significantly affect cloud microphysical processes, and in turn, several aspects of weather and climate. The aerosol-cloud interactions and its impact on climate is the least understood and therefore is a subject of intense research in recent years. For more details pertaining to the effects of aerosols on climate and on cloud processes and precipitation, one can look into the excellent reviews by (Lohmann and Feichter 2005;Rosenfeld et al. 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 47 publications
(43 reference statements)
1
11
0
Order By: Relevance
“…After clustering, the PM 1 chemical compositions corresponding to the BTs in each cluster were averaged, which is also shown in Figure . The BT analysis confirmed that the air masses sampled in this study predominantly arrived from the northwest, as reported in a previously conducted wintertime study at this location [ Patidar et al ., ]. BT analysis also indicates that the site is primarily affected by surface emissions as evident from the trajectory heights (Figure S10).…”
Section: Resultsmentioning
confidence: 99%
“…After clustering, the PM 1 chemical compositions corresponding to the BTs in each cluster were averaged, which is also shown in Figure . The BT analysis confirmed that the air masses sampled in this study predominantly arrived from the northwest, as reported in a previously conducted wintertime study at this location [ Patidar et al ., ]. BT analysis also indicates that the site is primarily affected by surface emissions as evident from the trajectory heights (Figure S10).…”
Section: Resultsmentioning
confidence: 99%
“…During real-time ambient sampling, the AMS also sampled submicron background interstitial ambient aerosols present at the site before or during a fog event, which were too small and/or Journal of Geophysical Research: Atmospheres 10.1002/2015JD024508 too hydrophobic to be activated into fog droplets. Generally, condensation nuclei for fog droplets are a fraction of the submicron aerosol population with activated fractions of <20-100%, depending on particle size [Frank et al, 1998;Patidar et al, 2012;Hammer et al, 2014]. Therefore, real-time ambient submicron AMS data and offline fog water AMS data can be compared to understand the extent of aqueous processing of organics inside fog droplets.…”
Section: Ams Measurementsmentioning
confidence: 99%
“…The major pollution sources in the winter season are vehicle emissions, industrial emissions, biomass burning, open area burning, coal power plants, and domestic cooking [Nair et al, 2007]. In addition, the site is also affected by long-range transported aerosols from the northwestern part of India, which experiences large numbers of forest fires [Patidar et al, 2012]. The estimated distance of the fire hot spots (shown in Figure 1) from the sampling location is approximately 700-1000 Km.…”
Section: Experiments and Theorymentioning
confidence: 99%
“…The AMS and CCN data averaging time is kept same as the SMPS scan time, i.e., 3 min, thus eliminating 2 and 4 min of CCN data at the start of lower (0.2%) and higher (0.4%-1.0%) SS values, respectively. A supersaturation depletion correction has been applied due to high CCN concentrations following the same approach as described in earlier studies [Lathem and Nenes, 2011;Patidar et al, 2012]. Hereafter, SS refers to depleted SS instead of measured SS.…”
Section: Ccn and Related Calculationsmentioning
confidence: 99%
See 1 more Smart Citation